Yamadazyma riverae sp. nov., a yeast species isolated from plant materials - Lopes, Mariana R.; Ferreira, Mariana C.; Carvalho, Tatiana F C [UNESP]; Pagnocca, Fernando C. [UNESP]; Chagas, Rafaella A.; Morais, Paula B.; Rosa, Luiz H.; Lachance, Marc-André; Rosa, Carlos A. (International Journal Of Systematic And Evolutionary Microbiology, 2015)
Nine strains of a novel yeast species were isolated from rotting wood, tree bark, ant nests or living as endophytes in leaves of Vellozia gigantea. Analysis of the sequences of the internal transcribed spacer (ITS) region and the D1/D2 domains of the large subunit rRNA gene showed that this species is related to Candida insectorum in the Yamadazyma clade. The new species differs from its closely related species by 10 and 11 substitutions in the ITS region and the D1/D2 domains of the large subunit of the rRNA gene, respectively. The species is heterothallic and forms asci with one to two hat-shaped ascospores. The name Yamadazyma riverae sp. nov. is proposed. The type strain of Yamadazyma riverae sp. nov. is UFMG-CM-Y444T (= CBS 14121) and the allotype strain is TT12 (= CBS 14098 = UFMG-CM-Y577). The Mycobank number is MB 813221.